Self-in-relationship psychotherapy in action : individual, couple, family and child psychotherapy - Meier, Augustine, 1933-; Boivin, Micheline, 1950- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book presents a comprehensive guide to applying Meier and Boivin's Self-in-Relationship Psychotherapy model to clinical work with individuals, couples, families and children. The central theme of the book is that the paradigm of affects, cognitive processes and behaviors that informs current psychotherapy approaches needs to be broadened to include core self, relational and physical intimacy needs as motivating factors in psychotherapy. Drawing on multiple influences including relational psychoanalysis, the authors illustrate how to work with core needs when providing therapy to children and adults. They establish that core needs are universal, and their realizations are essential for healthy living and argue that clients achieve the healthiest outcomes by finding a way to balance the self alongside their relations with others. The concept of core self, relational and physical intimacy needs is what binds all the chapters in this book and makes it unique among psychotherapy approaches. With a clear transtheoretical approach and rich clinical vignettes, this book is core reading for any psychotherapists, psychoanalyst, or practicing psychologists"--
Keywords: Self psychology; Interpersonal psychotherapy; PSYCHOLOGY / Movements / Psychoanalysis